THE EFFECT OF IGF-1 GENE POLYMORPHISMS ON SOME PHYSIOLOGICAL AND PRODUCTIVE PARAMETRS IN BROILER CHICKEN BREED COBB500. - A. S.A.AL-Hassani; M. H.AL-Suhail (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment investigated the association between SNP 5 UTR region of insulin –like growth factor-1 ( IGF-1 ) and phenotypic productive and physiological traits in cobb500 broiler breed .The study was conducted at poultry farm in Abu-Graib region during a period from 1Nov 2016-14Dec 2016 .Four hundred fifty broiler chicks one day old (cobb500) were wing –banded and divided to three treatment groups (three replicates each) according to gene polymorphisms .DNA was extracted from fresh blood samples .Restriction fragment length polymorphism was used in the 5 UTR region of IGF-1. Chicks were reared under conventional conditions according the guide and fed ad libitum at the end of experiment number of birds were killed to measure carcass cuts. Results showed a significant (P≤ 0.05) increase in live body weight of TT comparing with TC and CC in 1st week, whereas no significant differences was found between different polymorphisms in weight gain, blood traits and serum components in all weeks .on the other hand a significant (p≤ 0.05) increase was found in final body weight ,carcass weight and length of sternum and thigh bones for TT polymorphism in comparison with TC and CC.